2016
DOI: 10.1152/ajpregu.00459.2015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rate and rates of protein turnover in food-deprived cuttlefish,Sepia officinalis(Linnaeus 1758)

Abstract: To determine the metabolic response to food deprivation, cuttlefish (Sepia officinalis) juveniles were either fed, fasted (3 to 5 days food deprivation), or starved (12 days food deprivation). Fasting resulted in a decrease in triglyceride levels in the digestive gland, and after 12 days, these lipid reserves were essentially depleted. Oxygen consumption was decreased to 53% and NH4 excretion to 36% of the fed group following 3-5 days of food deprivation. Oxygen consumption remained low in the starved group, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 40 publications
4
22
0
Order By: Relevance
“…In systemic heart, HK activity was maintained at fed Data are mean ± SEM, n = 7-8. These data were previously published in Lamarre et al (2016) levels following short-starvation (two-way ANOVA, p > 0.05), but decreased by 28 % following longstarvation (two-way ANOVA, p < 0.05). HK activity in branchial heart was not measured in short-starved individuals, but following long-starvation levels were decreased by 21 % compared with fed controls (t test, p < 0.01).…”
Section: Enzymatic Capacities For Glycolysis and Anaerobic Glycolysissupporting
confidence: 86%
See 2 more Smart Citations
“…In systemic heart, HK activity was maintained at fed Data are mean ± SEM, n = 7-8. These data were previously published in Lamarre et al (2016) levels following short-starvation (two-way ANOVA, p > 0.05), but decreased by 28 % following longstarvation (two-way ANOVA, p < 0.05). HK activity in branchial heart was not measured in short-starved individuals, but following long-starvation levels were decreased by 21 % compared with fed controls (t test, p < 0.01).…”
Section: Enzymatic Capacities For Glycolysis and Anaerobic Glycolysissupporting
confidence: 86%
“…This general response is consistent with radiolabel and other studies in cephalopods that have suggested that a mix of metabolic fuels is used during early starvation, followed by a greater reliance upon lipids and amino acids in order to conserve carbohydrate stores (digestive gland glycogen is limited; mantle glycogen is reserved for fueling locomotion), and finally a large reliance upon amino acids once lipid stores are exhausted (O'Dor et al 1984;Castro et al 1992;Lamarre et al 2012). In fact, the responses of the ammonia quotient of our study animals suggested a transitory shift to lipid catabolism during short starvation and then to protein catabolism after long starvation, when triacylglycerol became depleted (Lamarre et al 2016). Layered upon the general response in cuttlefish was a tissue-specific response in which metabolic capacity in digestive gland and mantle appeared to be shut down more than in gill or systemic heart.…”
Section: Starvation Responses: Glycolytic Capacity Is Downregulated Wmentioning
confidence: 58%
See 1 more Smart Citation
“…This suggests that the higher mitochondrial density in the livers of fasted trout may be an adaptive component of the metabolic response to food deprivation (Secor & Carey, 2016). However, our results clearly show that the reduction in the total "number" of hepatic mitochondria drives a decrease in liver total oxygen requirements, and presumably partly explains the reduction of whole-body metabolism that occurs in response to food shortage Lamarre et al, 2016;Monternier et al, 2014).…”
Section: Discussionmentioning
confidence: 61%
“…Animals were then incubated for 1.5 hr in darkened containers bubbled with air. These conditions were shown to respect the assumptions of the flooding dose assay in this species (Lamarre et al, 2016). After this incorporation period, the animals were killed as previously described, and the treatment and reference arms from each animal were excised and flash-frozen in liquid nitrogen for further analysis.…”
Section: Surgery and Samplingmentioning
confidence: 99%